Telaah Praksis Pendidikan Agama Islam di Sekolah Dalam Pembentukan Karakter Siswa - Moch Iqbal (Tadbir : Jurnal Studi Manajemen Pendidikan, 2019)
This paper examines the strategic role of religious education in the national education system. In accordance with the mandate of UU Sisdiknas no 20/2003 that religious education is part of national education. Moreover, the issue of character education is getting stronger, increasingly placing religious education, in this case Islamic Education (IE) as the spearhead in guarding the implementation of character education. By using literature study, the results of this study were obtained, that the implementation of IE needs to be improved in order to produce students with character. Some obstacles in the implementation of Islamic religious education, making the PAI has not been able to produce students of character as much as expected by all parties. There are two dominant causes in the implementation of IE that are less than the maximum. First, IE puts more emphasis on the mastery of texts contained in textbooks and outer cognitive only (cognitive domain), whereas the substance of the cultivation of religious values just disappears as the cognitive knowledge accumulates. Second, the doctrinal learning process must be accepted, without growing the students' critical reason.